Fragile Hopes, Strong Minds: Self-Regulation and Emotion Regulation as Mediators between Basic Psychological Needs and the Psychological Well-Being of Children in Conflict with the Law - Yul Arifiana, isrida; Nur Fatwa, Ajang (Journal of Educational, Health and Community Psychology, 2025)
Children in Conflict with the Law (CCL) are a vulnerable group at risk of low psychological well-being due to social stigma, legal pressure, and limited developmental environments. This study aims to examine the influence of Basic Psychological Needs (BPN) on Psychological Well-Being (PWB) in CCL, with Self-Regulation (SR) and Emotion Regulation (ER) as mediating variables. A quantitative approach with a correlational design was used on 214 CCL participants aged 13–17 years who were undergoing developmental programs at the Special Child Development Institution (LPKA) and non-governmental organizations in Surabaya. The research instruments included the BSPWB-A to measure PWB, the BPNSFS for BPN, the Zimmerman model-based self-regulation scale for SR, and the ERQ-CA for ER. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS 4. The results showed that BPN had a positive and direct effect on PWB (β = 0.366; t = 5.665; p < 0.001). SR significantly mediated the BPN–PWB link (β_indirect = 0.125; t = 3.723; p < 0.001), indicating partial mediation, whereas ER did not mediate the relationship (βindirect = 0.125; t = 3.723; p < 0.001). These findings emphasize the importance of fulfilling basic psychological needs and strengthening self-regulation skills as practical strategies in improving the psychological well-being of CCL.